Hubungan Kelimpahan Plankton Dengan Pertumbuhan Ikan Bandeng (Chanos chanos Forskal) Di Tambak Tradisional Sidoarjo, Jawa Timur - Endang Yuli Herawati; Anik Martinah H.; Qurrota A'yunin; Rully Isfatul H. (Universitas Lambung Mangkurat, 2019)
The surrounding community activities in the area of milkfish ponds include residential and household waste so that it will affect the water source used for milkfish farms (Chanos chanos Forskal). Due to changes in water quality, it will be known how the condition of pond water quality will affect the abundance of phytoplankton and the growth of milkfish (Chanos chanos Forskal). This study aims to determine the relationship of plankton abundance with the growth of milkfish (Chanos chanos Forskal) in traditional ponds. The method used is the descriptive method. The study was conducted in March - May. The results of the regression analysis for plankton abundance found a relationship that affects a specific growth rate of 83% and 17% influenced by other factors. The correlation coefficient (r) obtained is 0.91 so that it can be said that the abundance of plankton influences the specific growth rate classified as strong. Based on the value of b = 0.0156x (positive relationship) means that if plankton abundance rises the rate of growth also increases by 0.015. If the plankton does not exist or 0 then the rate will decrease by 94.